A atividade probatória proativa do juiz: alcance e limites dos poderes instrutórios de ofício. - Dantas, Vanessa Andrade (2009)
Starting from a publicist conception of procedural law, which is considered to be an instrument for guaranteeing an effective jurisdictional tutelage, we cannot any longer admit the idea of a passive judge, a mere spectator of the activities on the side. In the current procedural conjuncture, we expect from the judge a proactive performance during the carrying out of the procedure, by studying the dogma of civil procedural law on the proactive probative practice of judges. The research begins with an analysis of the principal procedural systems by focusing on the practices of the judges during the procedures and examining also the fact-finding powers of the same judges during Brazilian civil procedures. It broaches the ground principies of the proactive probative practices of judges in civil proceedings. Some elementary notions on proof and the shedding of light on the distribution rules with regard to the burden of proof and its relation to the fact- finding powers of judges are also discussed. It analyses some classifications as shown by PhDs on the powers of judges when they are the State representative in the carrying out of judicial power. In this way, we understand that the fact-finding powers of judges in civil procedures must be very ample, and they must use ali their powers in the proactive performance in their search for the real truth. In the Brazilian legal system, the foundation for fact-finding powers of judges is in the CPC article number 130, moreover, other devices also give the judges specific fact-finding powers, however, constituting exclusive emphatic enumeration. Finally, we cannot forget that in arder to avoid abuse and trespassing by the judges, the judicial power itself foresaw limitations to the fact-finding activities by the magistrates, as they must observe the judicial principais in their carrying out of duties. In this way this dissertation sheds lights on the real proactive probative activity of judges, their ranges and limits.